Prototype Pembangkit Listrik Hybrid Tenaga Surya dan Bayu Sebagai Sumber Energi Terbarukan - Hanif Al Amri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to design and test a prototype of a hybrid power plant based on solar power (PLTS) and wind power (PLTB) as an environmentally friendly small scale renewable energy solution. The background of this research is based on the increasing need for electrical energy and the urgency of transitioning from fossil fuels to clean energy. The prototype is designed by integrating a 20 Wp monocrystalline solar panel and a Savonius-type vertical wind turbine connected to a 12V 4Ah battery via a charge controller. The system is configured in parallel to allow simultaneous charging from both energy sources. Tests are carried out separately on each component and integrated as a hybrid system. The parameters observed are voltage (V) and current (mA). The test results show that the PLTS produces a maximum voltage of 18.4 V with a current of 22.4 mA during the day, while the PLTB produces a maximum voltage of 13.1 V with a current of 15.98 mA at a wind speed of 17.2 km/h. The integration of the two systems is capable of providing a maximum total power of approximately 0.621 W. Although the power capacity is still limited, this system successfully demonstrates the complementary synergy between solar power plants (PLTS) and wind power plants (PLTB), thereby improving the continuity of energy supply. This prototype has the potential for further development for applications in remote areas and as a learning tool for renewable energy.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: renewable energy; hybrid power plant; solar panels; wind turbine; prototype.